Ethnobotany, Pharmacology, and Metabolomics of Antidiabetic Plants used by the Eeyou Istchee Cree, Lukomir Highlanders, and Q’eqchi’ Maya - Ferrier, Jonathan (Université d'Ottawa / University of Ottawa, 2014)
A study was undertaken of plants used for treatment of diabetic symptoms by traditional healers of the Eeyou Istchee Cree (Canada), Lukomir Highlanders (Bosnia & Herzegovina), and Q’eqchi’ Maya (Belize). All antidiabetic plants were ranked by syndromic importance value (SIV) based on 15 symptoms, all of which were recognized by the Cree and Maya and 8 by the Highlanders. The Cree used only 18 species, the Highlanders 41, and the Maya 150, numbers which reflect the diversity of flora in their region. Vaccinium (Ericaceae) was one of the few genera in all three regions and the only consensus genus between the Cree and Highlander study sites. The Q’eqchi’ Maya ethnobotany did not present any cross-cultural consensus genera with Cree or Highlander medicinal plants, perhaps due to major biogeographic differences. In ethnopharmacological studies, Vaccinium species and Q’eqchi’ antidiabetic plants were tested in an assay relevant to diabetes, the advanced glycation endproduct (AGE) inhibition assay. Boreal and tropical Vaccinium species were potent inhibitors of AGEs and demonstrated concentration dependent inhibition, with a half maximal inhibitory concentration (IC50) range of 5.93–100 µg/mL. Phenolic content ranged from 80.3 to 201 µg/mL in boreal samples and from 1470 to 2170 µg/mL in tropical samples. Tropical species have a greater phenolic content and AGE inhibition. Seven Q’eqchi’ antidiabetic plant species were tested and all plant extracts showed AGE-inhibition. The IC50s ranged from 40.8 to 733 µg/mL, and the most active was Tynanthus guatemalensis Donn.. Tynanthus guatemalensis IC50 was about fives times greater (less active) than the mean ± SE IC50 reported for six tropical Vaccinium species of Vaccinium (8.77 ± 0.79 μg/mL). The highest consensus and most active Maya antidiabetic plant, Tynanthus guatemalensis Donn. Sm. was discovered to be an important plant recorded in archeological artifacts from the Late Classic Maya period (~750 CE). Ancient Maya used a cross shaped sign (k’an glyph) as a decorative element on Late Classic polychrome vessels and murals. The sign was believed to be the xylem template for a plant used as a flavouring in cacao drinks. However, the plant was incorrectly identified in the literature as Pimenta dioica (L.) Merr. (common name: Allspice) based on a common name and aromatic plant quality – not from a botanical voucher specimen. Pimenta dioica wood does not have a cross shape visible in the xylem but a unique character visible after a cross section of T. guatemalensis, is the xylem's cross shape organization. Wood of T. guatemalensis' also has an "allspice" aroma. Tynanthus guatemalensis is most likely the true botanical template behind the ancient Maya k’an glyph and this finding would show the continuity of use of this medicinal plant from ancient to modern times. Vaccinium was selected for an in depth phytochemical analysis using modern metabolomic methods. Nuclear magnetic resonance (1H NMR) was used to evaluate leaf extract spectra to provide information on (1) the taxonomic identity and (2) quantities of bioactive metabolites across multiple sites. Spectra clearly differentiated leaf samples of V. angustifolium, V. boreale, V. corymbosum, V. macrocarpon, V. myrtilloides, V. myrtillus, V. ovalifolium, and V. uliginosum according to generic, subgeneric, specific, phenotypic circumscriptions. Quantification of chlorogenic acid and hyperoside were replicated with a method that is highly reproducible across multiple sites with different NMR equipment. This methodology provides an important new approach to taxonomy and quality control for plants and natural health products.
Keywords: Ethnobotany; Pharmacology; Metabolomics; Lukomir, Bosnia and Herzegovina; Post war ethnobotany; Diabetes; Q'eqchi' Maya; Eeyou Istchee Cree; Syndromic importance value (SIV) (correction); Advanced glycation endproducts; UPLC MS QTOF; Nuclear Magnetic Resonance (NMR); Chemotaxonomy; Phylogenetic tree; Vaccinium; Ericaceae; Tynanthus guatemalensis; Allspice; Chibayal; K'an hieroglyph template; Lukomir Highlanders; Pimenta dioica; Cross-cultural ethnobotany; Toledo District Belize; Eeyou Istchee Territory; Canadian Institutes of Health Research Team for Aboriginal Antidiabetic Medicine (CIHR TAAM); Traditional Medicine; Chemosystematics; Metabolomic fingerprinting; Metabolomic leafprinting